Bochdalek hernias in children with late presentation - Tartar, Tugay; Sarac, Mehmet; Bakal, Unal; Kazez, Ahmet (Turkish Pediatrics Assoc, 2018)
Aim: Bochdalek hernias, which brought after the neonatal period, are also late-defined cases. In this study, we aimed to present the clinical characteristics of patients with late-presentation Bochdalek hernias who underwent surgery in a reference hospital and our experience regarding their diagnosis. Material and Methods: Patients with late-presentation Bochdalek hernia who underwent surgery in our clinic between 2001 and 2016 were analyzed retrospectively in terms of the causes of the delay in diagnosis, symptoms, and radiologic and surgical results. Results: A total of seven patients with late-presentation Bochdalek hernia underwent surgery, four males and three females. The median age was 48 months. Of the 43 patients who underwent surgery for Bochdalek hernia during the same period, 7 (1627%) presented to hospital late. In all late-presentation Bochdalek hernia cases., the defect was on the left. side. TWo patients had hernia sacs, and two patients had ectopic intrathoracic left kidneys. Six of the patients presented with gastrointestinal system symptoms, and one with respiratory system symptoms. The median time between the onset of symptoms and diagnosis was 60 days. The maternal age of four patients was >= 30 years.The gestational age and birth weights of the patients were normal. In physical examination, there was a scaphoid abdomen and an increased chest anterior-posterior diameter. In chest radiographs of all patients, the appearance was consistent with intestinal gas in the left hemithorax. The transverse length of the defect in the diaphragm (median value: 5 cm) in the patients with late-presentation Bochdalek hernia was longer than that (median value: 3 cm) of patients who were diagnosed early (p=0.02). The difference was statistically significant. All patients survived, were followed up for an average of 3 years, and no relapse was observed during the follow-up period. Conclusion: Bochdalek hernia can be diagnosed after the neonatal period. Contrary to cases diagnosed in the neonatal period, gastrointestinal system symptoms are at the forefront in these cases, and these patients have good prognosis. Congenital diaphragmatic hernia should be considered in the differential diagnosis in patients with gastrointestinal system symptoms such as recurrent nausea and vomiting.
Çocuklarda geç başvurulu Bochdalek hernileri
Keywords: Bochdalek hernia; Congenital diaphragmatic hernia; child late presentation